PENGARUH BRAND COMMUNITY TERHADAP LOYALITAS MEREK PADA PENGGUNA SEPEDA MOTOR VESPA (Survei Pada Pengguna Vespa Matic Piaggio di Media Instagram @SpeedingIndo - Evan Elfian Suseno, (2020)
This research discusses the influence of brand community on brand loyalty of Vespa Piaggio motorcycle in media community Vespa Speeding Indonesia. The purpose of this research is to know hot much influence the brand community on brand loyalty. The theory used in this study is Reasoned Action Theory. The basic concept of brand community is divided into three pilars, namely consciousness of kind, shared rituals and tradition, and sense of moral responsibility. This research used a quantitative approach with a survey by distributing questionnaires to 100 followers of Vespa Speeding Indonesia in Instagram that who had been using Vespa Piaggio and had at leaset been following the community activities at least once. The result of this study showed that the brand community has a significant influence on Vespa Piaggio in the media community of Vespa Speeding Indonesia.